Unjust Disparities? The Impact of Race on Juvenile Risk Assessment Outcomes - McCafferty, James T. (Criminal justice policy review, 2018)
Research on risk assessments has illustrated many utilitarian purposes of these tools, including the robust prediction of recidivism and uniformity in correctional decision making. Recently, however, Former U.S. Attorney General Eric Holder vocalized his position that actuarial risk assessments could be unintentionally contributing to disproportionate minority contact in the correctional system. This study used data from approximately 2,600 juvenile delinquents assessed with the Ohio Youth Assessment System-Disposition Instrument to examine these claims across subsamples of White and Black youth. Bivariate and multivariate analyses indicated that the instrument predicted recidivism similarly across the two groups. There were slightly more prediction errors for Black youth than White youth; however, these differences may be the result of methodological factors rather than empirical realities. The article concluded with a discussion of the implications that potential racial biases have on risk assessment research and practice.